Butyricicoccus plays a key role in mediating the antagonism between probiotic and antibiotic on food allergy. Issue 1 (1st January 2019) - Wang, Yanbo; Wang, Chong; Huang, Jianjian; Xie, Menghua; Li, Xiuting; Fu, Linglin
ABSTRACT: Food allergy is a severe food safety problem worldwide. Probiotics are effective in alleviating food allergy whereas antibiotics may exacerbate allergenic responses, but the knowledge on the interplay between them during food allergy is limited. In the present study, we investigate the activity of probiotic strain Lactobacillus casei (Lc) and antibiotic cocktail (Abx) on in a food allergy mouse model. The results showed that Lc relieved allergenic symptom and changed allergen-specific antibodies isotypes. Moreover, Lc upregulated chemokines in the spleen, and promoted regulatory CD103+ DC and IgA-producing B cell proliferation. In contrast, the application of Abx eliminated all these beneficial effects of Lc. Microbiota analysis revealed that the commensal genus Butyricicoccus was a critical mediator in the process. These results revealed the mechanisms of Lc and Abx interaction on food allergy and provided Butyricicoccus as a potential therapeutic target for food allergy.